MELIHAT KEMBALI RADIKALISME ISLAM DI INDONESIA DAN UPAYA-UPAYA PENCEGAHANNYA - Turmudi, Endang (P2KK LIPI, 2012)
Radicalism embraced by a smallgroup of Muslims in Indonesia continues to develop and their radical actions increased significantly, as can be seen from the bombing of some hotels, churches and even mosques. Radicalism is influenced by an ideology which among others opposes the presence o f(Secular) Indonesian States, considers other Muslims outside their own group as infidels and exerts to establish an Islamic state. Furthermore, the radicals tolerate violence and even terrorism in order to achieve what they pursue. Since radicalism deals with ideology, the effort of de-radicalization is to unplug certain Islamic understanding of the radicals. Without such direction, deradicalization seems to be difficult to achieve, given the fact that changing ideology is impossible. Therefore, experts proposed a program of